Partial dictation as a measure of EFL listening proficiency: Evidence from confirmatory factor analysis. (April 2013) - Cai, Hongwen
Partial dictation is a measure of EFL listening proficiency that can be easily constructed, administered, and scored by EFL teachers. However, it is controversial whether this form of test measures lower-order abilities exclusively or involves both lower- and higher-order abilities. In order to answer this question, a study was designed to examine the difference between partial dictation and test forms believed to measure more higher-order abilities. In a series of confirmatory factor analyses, the simplex, second-order, and bi-factor models were fitted to the scores of 367 college-level EFL learners in China in a listening test composed of partial dictation, gap-filling and constructed response tasks. The bi-factor model was identified as the best-fitting and this supports the view that partial dictation measures the same construct as test forms believed to measure more higher-order abilities. Concomitant statistical analyses also showed that the partial dictation tasks were suited to the ability level of the test takers and had high internal consistency.